Lean Implementation in Indonesian Small and Medium Enterprises: A Systematic Literature Review - Difana Meilani; Hasnida Ab Samat (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2024)
Lean implementation focuses on reducing waste and improving efficiency in business operations, a strategy widely embraced in developed countries. However, its adoption among Indonesian SMEs is limited and lacks adequate research. Understanding how lean practices can effectively enhance competitiveness and productivity in this vital sector of the Indonesian economy is crucial. Despite its widespread use in Western countries, there's a noticeable gap in research specifically examining how lean principles are applied within SMEs, especially in developing countries like Indonesia. Furthermore, there's a clear scarcity of studies detailing the current state of lean implementation in Indonesia, particularly within SMEs. This study conducted a systematic literature review (SLR), thoroughly searching peer-reviewed journals and conference papers. We identified 441 articles related to lean practices in Indonesia, with 40 focusing specifically on SMEs. Through this review, we uncovered key themes and trends in lean implementation, offering valuable insights into current practices and highlighting areas for future research. This paper represents one of the first comprehensive SLRs exploring lean practices within Indonesian SMEs. It aims to deepen our understanding of how lean methodologies impact SME operations in Indonesia and provides practical guidance for researchers and practitioners interested in lean implementation. By bridging these research gaps, we hope to contribute to the body of knowledge on lean implementation in Indonesian SMEs, suggesting strategies for effective implementation and paving the way for further study in this important area.